Advantages of Producing Aromatics from Propene over Ethene Using Zeolite‐Based Catalysts. Issue 11 (11th October 2022) - Butolia, Paresh S.; Xi, Xiaoying; Winkelman, Jozef G. M.; Stuart, Marc C. A.; van Akker, Matthijs; Heeres, André; Heeres, Hero Jan; Xie, Jingxiu
Abstract: Sustainable production of aromatics, especially benzene, toluene and xylenes (BTX), is essential considering their broad applications and the current global transition away from crude oil utilization. Aromatization of lower olefins, particularly ethene and propene, offers great potential if they are derived from more circular alternative carbon feedstocks such as biomass and waste plastics. This work aims to identify the preferred olefin feed, ethene or propene, for BTX production in a fixed‐bed reactor. A commercial H‐ZSM‐5 (Si/Al = 23) catalyst was used as a reference catalyst, as well as a Ga‐ZSM‐5 catalyst, prepared by Ga ion‐exchange of the H‐ZSM‐5 catalyst. At 773 K, 1 bar, 45 vol % olefin, 6.75 h −1, propene aromatization over the Ga‐ZSM‐5 catalyst exhibited higher BTX selectivity of 55 % and resulted in slower catalyst deactivation compared to ethene aromatization. Abstract : Aromatization of lower olefins is a viable, circular route to produce benzene, toluene and xylenes (BTX). We investigated the conversion of ethene and propene to aromatics using commercial and Ga‐promoted ZSM‐5 catalysts. Propene was found to be a more superior feed than ethene, as higher BTX yields and catalyst lifetimes were attained.